Discovering Addiction The Science and Politics of Substance Abuse Research - Campbell, Nancy D. (University of Michigan Press, 2007)
Discovering Addiction brings the history of human and animal experimentation in addiction science into the present with a wealth of archival research and dozens of oral-history interviews with addiction researchers. Professor Campbell examines the birth of addiction science---the National Academy of Sciences's project to find a pharmacological fix for narcotics addiction in the late 1930s---and then explores the human and primate experimentation involved in the succeeding studies of the "opium problem," revealing how addiction science became "brain science" by the 1990s.